Neighborhood cohesion and psychological distress across race and sexual orientation - Gabe H. Miller; Guadalupe Marquez-Velarde; Erika-Danielle Lindstrom; Verna M. Keith; Lauren E. Brown (Elsevier, 2022)
Introduction: We investigate the association neighborhood cohesion, as source of social support, has with psychological distress among white, Black, and Latinx lesbian, gay, and bisexual (LGB) individuals, compared to heterosexual individuals in the United States. Method: We estimate zero-order multinomial logistic regression models to assess the likelihood of moderate and severe psychological distress among respondents. Result: In the models accounting for neighborhood cohesion and all other covariates, white, Black, and Latinx lesbian, gay, and bisexual individuals are more likely to meet the criteria for moderate and severe psychological distress than non-LGB people. Conclusion: Neighborhood cohesion has differing impact on psychological distress outcomes by racial/ethnic-sexual orientation groups, but in general provides a greater magnitude of protection against moderate psychological distress for non-LGB groups and a greater magnitude of protection against severe psychological distress for LGB groups.